2020
DOI: 10.1108/jpbm-03-2018-1782
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of brand credibility in consumer evaluation of global brands and domestic brands in an emerging market context

Abstract: Purpose The purpose of this study is to examine the impact of brand credibility on purchase intentions toward global brands and domestic brands in an emerging market context. It further examines three drivers of brand credibility: perceived globalness, perceived local iconness and perceived authenticity. Design/methodology/approach A structured questionnaire was used for data collection. Systematic random sampling using the mall intercept technique was used to collect cross-sectional data from 836 customers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 70 publications
(95 reference statements)
0
47
0
Order By: Relevance
“…In a CRM context, a critical factor in managing long-term relations with customers is brand credibility. Recent findings by Srivastava et al (2020) and Shams et al (2017) saw a significant and positive connection between purchase intention and brand credibility. Jamshidi and Rousta (2021) also found that the brand–consumer relationship depicted by the image and credibility of the brand significantly affects customer satisfaction.…”
Section: Brand Credibility Customer Satisfaction and Commitmentmentioning
confidence: 90%
“…In a CRM context, a critical factor in managing long-term relations with customers is brand credibility. Recent findings by Srivastava et al (2020) and Shams et al (2017) saw a significant and positive connection between purchase intention and brand credibility. Jamshidi and Rousta (2021) also found that the brand–consumer relationship depicted by the image and credibility of the brand significantly affects customer satisfaction.…”
Section: Brand Credibility Customer Satisfaction and Commitmentmentioning
confidence: 90%
“…Vietnam as an emerging tourism market, needs to develop its competitiveness to attract international tourists (Kandampully and Solnet, 2019). The characteristics of emerging markets, including the high level of market discrepancy and inadequate infrastructure and incomplete information, affect customer behavior (Srivastava et al, 2020). Therefore, with successful replication, this study and its results may be generalized to other similar destinations.…”
Section: Managerial Implicationsmentioning
confidence: 94%
“…Many of these studies have been centered on relationship marketing and provide the most insights into relation exchanges (Yoganathan et al, 2015). Trust is created in many different ways but is usually rooted in utilitarian and hedonic sources, including perceived quality, prestige and identitybased components of shared values, goals and cultural heritage (Huaman-Ramirez et al, 2019;Srivastava et al, 2020).…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 99%